RELIGIOUS TOLERANCE IN THE SUGDIYANA REGION - Mukhtorov Azizjon Botir ugli (Web of Journals Publishing, 2024)
This article provides detailed information about the history of religious tolerance in the Sugdiyana region, its current status and its role in social life. Important factors in ensuring religious tolerance in the region and their impact on social stability are considered.
Keywords: Sugdiyona region, religious tolerance, peoples, cultures, ethnic groups, social stability, local population.